Determinants of Non-Performing Loans: Perception of Nepali Bankers - Bhattarai, Seema (Economic Journal of Development Issues, 2016)
The paper discusses the perception of Nepalese bankers regarding the determinants of nonperforming loan in Nepalese commercial banks. The paper is based on primary information collected from 140 bankers working in large ten commercial banks of Nepal. The bankers of Nepalese commercial bank perceive that energy crisis; lack of timely budgetary expenditure by the government and instable political environment increases the non-performing loan. Similarly bankers also perceive that borrowers honesty in disclosing the information, better monitoring and evaluation of the loan, have significant negative impact on non-performing loan. However, the banker’s perception shows that the macroeconomic variables like unemployment rate, inflation rate, exchange rate and interest rate are not much important variables to influence non-performing loan of the commercial banks of Nepal. The bankers also perceive that the increase in GDP growth rate decrease the non-performing loan of commercial banks in Nepal. Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 128-148